Alarming evidence of widespread mite extinctions in the shadows of plant, insect and vertebrate extinctions. (28th August 2020) - Sullivan, Gregory T.; Ozman‐Sullivan, Sebahat K.
Abstract: This paper, which addresses the issue of the extinction of mite species at the global scale for the first time, highlights mite diversity, assesses the evidence for an extinction process, discusses contributing factors and estimates losses. The ~1 250 000 mite species occupy an enormous variety of terrestrial and freshwater ecosystems from the equator to the polar regions and to high altitudes. Some groups provide essential ecosystem services, including the incorporation of organic matter into the soil. The maintenance of mite diversity is inextricably linked to the continuance of floristic diversity, habitat complexity and insect diversity. The majority of mite species are assumed to be in the tropical rainforests, of which >50% has been destroyed or severely degraded. Most biodiversity hotspots are in tropical forests; endemic phytoseiid mite species are at least 17 times more concentrated in the hotspots than outside. Habitat destruction and degradation continue on an enormous scale, with increasing human population growth and resource consumption the overarching drivers of extinction. Moreover, climate change is likely to be worsening the effects of the other drivers at an increasing rate. The small body of direct evidence and a considerable body of indirect evidence strongly suggest the continuing, widespread extinction of mite species. Based on estimates of overall biodiversity loss, ~15% of mite species were likely to have become extinct by 2000, with losses currently expected to increase by between 0.6% and 6.0% by 2060. More detailed information on both spatial differences in mite assemblages and anthropogenic threats worldwide is crucial because they underpin the total number of species and their vulnerability to extinction, respectively. The rapid expansion of the protected area estate to capture the maximum possible area of ecosystem heterogeneity, especially in the biodiversity hotspots, is essential, as is best practice management of these areas.